A functionalized multi-walled carbon nanotube-based composite monolith as a solid-phase extraction adsorbent for on-line purification and enrichment of ursolic acid in medicinal plants. Issue 5 (8th January 2020) - Yu, Huan; Liu, Haiyan; Yang, Chunliu; Pang, Xiaoya; Zhang, Miaomiao; Yan, Hongyuan; Bai, Ligai; Han, Dandan
Abstract : A hybrid monolith was prepared and used as a sorbent for online enrichment and purification of ursolic acid from medicinal plants. Abstract : A novel poly(f-MWCNTs- co -ST- co -EDMA) monolith was prepared using functionalized multi-walled carbon nanotubes (MWCNTs) and styrene (ST) as comonomers and ethylene glycol dimethacrylate (EDMA) as the crosslinker. The surface morphology and internal structure of the monolith were determined by scanning electron microscopy (SEM), nitrogen adsorption–desorption isotherm and mercury intrusion porosimetry. The monolith possessed a homogeneous and continuous structure and large surface area. The monolith was used as the sorbent for on-line enrichment and purification of ursolic acid. The linear range was 0.0002–3.5 mg mL −1 ; the limit of detection (LOD) and the limit of quantitation (LOQ) were 0.52 μg mL −1 and 1.72 μg mL −1, respectively. The intra-day and inter-day precisions, which were expressed as the relative standard deviation (RSD), were no more than 0.76% and 1.51%, respectively. The recoveries were between 94.05% and 109.68% in several medicinal plants. The composite monolith showed low back pressure and high adsorption capacity for the enrichment and purification of ursolic acid.